Therapeutic strategy in acute myeloid leukemia – the experience of a single Portuguese institution - Ana Espirito Santo; Sergio Chacim; Luis Leite; Isabel Cristina; Claudia Moreira; Dulcineia Pereira; Margarida Dantas; Marta Nunes; Luisa Viterbo; Angelo Martins; Ilidia Moreira; Isabel Oliveira; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
BackgroundAcute MyeloidLeukemia is a clonal malignant disease, whit disappointing cure rates withcurrent treatment options. The authors’ intent to characterise acute myeloidleukaemia patients and to evaluate the outcome gain associated with the use ofantagonists of P-glycoprotein in induction regimens.Patients andmethodsThe authorsgathered the epidemiological features, disease traits and outcome of 185patients, diagnosed with Acute Myeloid Leukemia (AML), treated at InstitutoPortuguês de Oncologia – Porto, Portugal, since 1998 until December 2010. Patients can betreated according to two possible schemes: “SWOG 9126” (cytarabine,daunorubicin and cyclosporine) regimen used when dysplastic changes are presentor “idarubicin and cytarabine” performed on the remaining ones. ResultsSome importantdifferences were found in relevant clinical features in both groups (age,disease classification) that can influence outcome. Nevertheless the two groupsoverlap in other also prognostic relevant traits (cytogenetic, riskstratification).Overall survivaland disease free survival were assessed: relevant differences were found,favouring the use of “idarubicin and cytarabine” protocol over “SWOG 9126”protocol.In the presenceof secondary leukemia or previous myelodysplasia no gain was achieved with theuse of SWOG 9126.ConclusionThe authorsdemonstrate the lack of gain in OS associated to the use of “SWOG 9126”treatment when compared to “idarubicin and cytarabine” regimen, with moreprofound and long lasting responses in the latter that the ones achieved withthe use of SWOG 9126.  This reducedefficacy is also encountered when dysplastic changes are met.